2016
DOI: 10.1152/physiolgenomics.00082.2016
|View full text |Cite
|
Sign up to set email alerts
|

Serum response factor induces endothelial-mesenchymal transition in glomerular endothelial cells to aggravate proteinuria in diabetic nephropathy

Abstract: We investigated the expression and function of serum response factor (SRF) in endothelial-mesenchymal transition (EndMT) in glomerular endothelial cells (GEnCs) of diabetic nephropathy (DN). The expression of SRF, endothelial markers (VE-cadherin, CD31), and mesenchymal markers (α-SMA, FSP-1, fibronectin) was examined in GEnCs following high glucose or in renal cortex tissues of DN rats. SRF was upregulated by SRF plasmids and downregulated by CCG-1423 (a small molecule inhibitor of SRF) to investigate how SRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Decreased GEnCs causes glomerular filtration dysfunction and proteinuria [26]. More important, EndMT plays a vital role in endothelial dysfunction, which [2,27]. In our study, we found that melatonin suppressed EndMT of GEnCs in diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 51%
“…Decreased GEnCs causes glomerular filtration dysfunction and proteinuria [26]. More important, EndMT plays a vital role in endothelial dysfunction, which [2,27]. In our study, we found that melatonin suppressed EndMT of GEnCs in diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 51%
“…He et al (35) demonstrated that SRF promotes EMT in human peritoneal mesothelial cells. SRF also provokes EMT in renal tubular epithelial cells of diabetic nephropathy (36), and it induces EMT in hepatocellular carcinoma, prostate cancer, and gastric cancer (37). Therefore, SRF has a significant role in EMT and cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that SRF is closely correlated to renal fibrosis in diabetic nephropathy and plays an important role in EMT in many types of renal cells, such as podocytes, 23 TECs 3 and glomerular endothelial cells. 24 Remarkably, SRF level and activation were increased in RCC cells (Fig. 2).…”
Section: Discussionmentioning
confidence: 81%